Designing and Developing a New Model of Education Surau and Madrasah Minangkabau Indonesia - Haviz, M (Jurnal Pendidikan Islam, 2017)
The purpose of this research was to design and develop a new model of education surau and madrasah Minangkabau (SMM) Indonesia. The method used is educational design research with phase: preliminary research, prototyping phase, and assessment phase. The participants of this research are 120 social religious activists as practitioners and 3 experts. The instrument used is validation and observation sheets. Means and standard deviation are calculated for finding the level of validity and observation of the implementation of the prototype. The result shows that the characteristics of the prototype are an organization, Minangkabau knowledge, pedagogical competencies, and social awareness. A process of design, a new model education SMM develops based on reality and good practical education. At the construction of the model, a new model education SMM is constructed by a specific program. At modernization of the education system, a new model education SMM must consist of Islamic and indigenes Minangkabau value. At flexible pedagogies and intervention, a new model education SMM requires new pedagogical ideas or themes and a special intervention from Islamic universities and stakeholders. In conclusion, design and develop a new model SMM Indonesia have the relevancy and internal consistency to stop the "stationary phase or run slowly" of surau and madrasah.